Y-Maze memory task in zebrafish (Danio rerio): The role of glutamatergic and cholinergic systems on the acquisition and consolidation periods - COGNATO, GIANA DE P. (2022)
Submitted by Biblioteca Suporte PUCRS (biblioteca.suporte@pucrs.br) on 2022-08-31T14:25:02Z No. of bitstreams: 2 YMaze_memory_task_in_zebrafish_Danio_rerio_The_role_of_glutamatergic_and_cholinergic_systems_on_the_acquisition_and.pdf: 898400 bytes, checksum: 749d2286c1df99f966cc528c3d838ca5 (MD5) YMaze_memory_task_in_zebrafish_Danio_rerio_The_role_of_glutamatergic_and_cholinergic_systems_on_the_acquisition_and.pdf: 898400 bytes, checksum: 749d2286c1df99f966cc528c3d838ca5 (MD5)